2008
DOI: 10.1007/s10725-008-9279-2
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of fruit set, parthenogenesis induction and fruit expansion in Japanese pear

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 35 publications
4
32
0
Order By: Relevance
“…Nakamura, T. Moriguchi and I. Nakajima early non-13-hydroxylated GAs such as GA 4 and GA 7 (Ito et al, 1999), whereas other bioactive forms of early 13-hydroxylated GA 1 /GA 3 have no effect on fruit size (Nakagawa et al, 1979;Zhang et al, 2008), a finding that is in accordance with our result. Zhang et al (2008) applied GA 1 , GA 3 , GA 4 , and GA 7 to Japanese pear fruit, and reported that their effectiveness for fruit enlargement is GA 4 ≈ GA 7 > GA 3 > GA 1 . Nakagawa et al (1979) showed that GA 4 is more abundant than GA 7 in pear fruit; therefore, we hypothesized in this study that the positive effect of GA 4+7 treatment on fruit enlargement (if any) would be due to GA 4 and not GA 7 .…”
supporting
confidence: 92%
See 4 more Smart Citations
“…Nakamura, T. Moriguchi and I. Nakajima early non-13-hydroxylated GAs such as GA 4 and GA 7 (Ito et al, 1999), whereas other bioactive forms of early 13-hydroxylated GA 1 /GA 3 have no effect on fruit size (Nakagawa et al, 1979;Zhang et al, 2008), a finding that is in accordance with our result. Zhang et al (2008) applied GA 1 , GA 3 , GA 4 , and GA 7 to Japanese pear fruit, and reported that their effectiveness for fruit enlargement is GA 4 ≈ GA 7 > GA 3 > GA 1 . Nakagawa et al (1979) showed that GA 4 is more abundant than GA 7 in pear fruit; therefore, we hypothesized in this study that the positive effect of GA 4+7 treatment on fruit enlargement (if any) would be due to GA 4 and not GA 7 .…”
supporting
confidence: 92%
“…Ito, D. Sakamoto, A. Itai, T. Nishijima, N. Oyama-Okubo, Y. Nakamura, T. Moriguchi and I. Nakajima early non-13-hydroxylated GAs such as GA 4 and GA 7 (Ito et al, 1999), whereas other bioactive forms of early 13-hydroxylated GA 1 /GA 3 have no effect on fruit size (Nakagawa et al, 1979;Zhang et al, 2008), a finding that is in accordance with our result. Zhang et al (2008) applied GA 1 , GA 3 , GA 4 , and GA 7 to Japanese pear fruit, and reported that their effectiveness for fruit enlargement is GA 4 ≈ GA 7 > GA 3 > GA 1 .…”
supporting
confidence: 91%
See 3 more Smart Citations